The cost analysis of steel halls designing, according to environmental standards, legal guidelines and market prices - Rogalska, Magdalena; Hejducki, Zdzisław (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The article presents the analysis of designing costs , which was based on the market data and prognostic calculations, concerning the preparation of the documentation for steel halls of various sizes. The obtained values were compared to those proposed by the Polish Architects Association and legal guidelines. The StatSoft’s Statistica programme was used for prognostic calculations. The GAM (Generalized Additive Models) method was used for the calculations. The conclusions were formulated on the basis of analysis of results.